The role of fibroblast growth factor (FGF) signaling in tissue repair and regeneration - Farooq, Mariya; Khan, Abdul Waheed; Kim, Moon Suk; Choi, Sangdun (Cells, 2021)
Fibroblast growth factors (FGFs) are a large family of secretory molecules that act through tyrosine kinase receptors known as FGF receptors. They play crucial roles in a wide variety of cellular functions, including cell proliferation, survival, metabolism, morphogenesis, and differentiation, as well as in tissue repair and regeneration. The signaling pathways regulated by FGFs include RAS/mitogen-activated protein kinase (MAPK), phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K)–protein kinase B (AKT), phospholipase C gamma (PLCγ), and signal transducer and activator of transcription (STAT). To date, 22 FGFs have been discovered, involved in different functions in the body. Several FGFs directly or indirectly interfere with repair during tissue regeneration, in addition to their critical functions in the maintenance of pluripotency and dedifferentiation of stem cells. In this review, we summarize the roles of FGFs in diverse cellular processes and shed light on the importance of FGF signaling in mechanisms of tissue repair and regeneration.
Keywords: Animals; Fibroblast Growth Factors; Humans; Models, Biological; Organ Specificity; Receptors, Fibroblast Growth Factor; Regeneration; Signal Transduction; Cell differentiation; Cell proliferation; FGF; FGFR; Tissue regeneration; Tissue repair